Autism : the road back - Bartlett, Sharon; LeRose, Maria; Knowledge Network (B.C.); FeelSales (Firm) ([Burnaby, Canada] : Knowledge Network, 2005)
Explores the assessment, diagnosis, and options of Autism Spectrum Disorder in children.
Originally released as a motion picture in 2005.
Narrator: Maria LeRose.
Cinematographers, Craig Hodge, Brian Sprout ; editor, Michael Taylor; music, Lesley Sutherland.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 25, 2016).
Keywords: Childhood disintegrative disorder; Autism in children; Asperger's syndrome; Autistic children -- Services for; Asperger's syndrome -- Patients -- Services for; Documentary films; Internet videos; Streaming video